“Prevalencia del síndrome del túnel carpiano en la práctica odontológica profesional en el distrito 06d01 Chambo Riobamba” - Galo Efraín, Andino Asitimbay (2020)
The general objective of this research was to analyze the prevalence of carpal tunnel syndrome in dentists working in the 06D01 Chambo Riobamba Health District. To carry out the research, we worked with a population made up of 53 dentists who work in the district, they met the inclusion and exclusion criteria. The mythological design was descriptive, bibliographic, comparative, cross-sectional and with a quantitative design. In order to process the information obtained in the development of the research work, frequency descriptive tables and graphs, Kolmogorov – Smirnov normality test and Chi-square statistical analysis of the SPSS program were used. In the results it was observed that in most participants, the prevalence of symptoms of carpal tunnel syndrome was absent or unlikely, of 49.1% in 26 dentist, followed by 37.7% in 20 dentists, and finally of a diagnosis classic, of 13.2% in 7 dentist, result that is encouraging to know that it was low, however it should not be overlooked and the definitive diagnosis should be made, however the percentage of dentists who present a diagnosis must also be taken into a account as possible to opt for preventive measures before the development od carpal tunnel syndrome. Concluding that in most od the dentists working in the 06D01 Chambo Riobamba Health District, there is an absent or unlikely symptomatology.